LEVERAGING INTERNET RESOURCES TO ENHANCE LANGUAGE SKILLS OF YOUNG LEARNERS (Innovative Technologica: Methodical Research Journal, 2023)
This article examines the benefits and drawbacks of using internet resources for language learning, particularly for young learners. The study explores different types of online resources such as interactive games, videos, podcasts, and language learning apps, and how they can be used to support language learning in a fun and engaging way. The benefits of using internet resources include increased motivation and accessibility, and the potential for learners to practice their language skills with native speakers from around the world. However, there are also potential drawbacks and challenges, such as exposure to inappropriate content and the need for proper guidance and supervision. Incorporating internet resources into traditional classroom instruction can be an effective way to complement and enhance language learning, but it is important to consider potential challenges and limitations such as internet access and the risk of distraction. Overall, the article emphasizes the importance of monitoring and guiding learners’ use of internet resources to ensure their safety and well-being.